The failure mechanics analysis of the solid self-piercing riveting joints. (January 2015) - Mucha, Jacek
Graphical abstract: Highlights: The respectively chosen force is required to achieve correctly formed joint. Too high value of SSPR joint forming force causes excessive residual stress increase in the rivet. The grooves of the solid rivet are stress concentrators in SSPR joint. The rivet head may fracture while tensioning the joint. Abstract: This paper presents the analysis of residual stress origin and its effect on rivet failure in the self-piercing riveting joints. The FEM method was used to analyze the residual stress distribution in the rivet. The effect of maximum joint forming force value on its maximum strength and residual stress distribution in the rivet was described. By increasing the SSPR rivet forming force the joints strength was increased. However, the pressing process with high value of the forming force is high-energy and accumulates significant residual stresses in the rivet. The maximum axial stress increased by 14% when the forming forces increased from 32 kN to 36 kN (increase by 12.5%). The theoretical considerations on safety coefficient determination for the rivet material were also presented. The fracture mechanics of elastic–plastic model body was characterized by using the energy state equations. The numerical calculations of J -integral, for two cases of maximum forming force in selected grooves in the rivet, were also presented. The energy release intensity in the stress concentrator (grooves on the rivet) was higher for the higher value of the forming force. The J -integral value for the forming force of 36 kN increased by 48% in comparison to the forming force value of 32 kN.